Household dairy production, dairy intake, and anthropometric outcomes in rural Bangladesh - Bakhtiar, M. Mehrab; Hoddinott, John F. (Elsevier, 2023)
We assess whether ownership of dairy cows is associated with a greater likelihood of consuming dairy products and with child anthropometric status in rural Bangladesh. Consistent with the assumption of imperfectly functioning markets for dairy products, ownership of dairy cows increases the likelihood that a child 6–59 months consumes milk by 7.7 percentage points with no difference in this association between boys and girls. This association nearly doubles in magnitude when we consider households that own a dairy cow that produced milk in the last year. This result is robust to the controls we use and the way in which we measure dairy cow ownership. Even when we saturate our model with child, maternal, household, wealth, as well as village fixed effects, we retain an association between dairy cow ownership and height-for-age z scores (HAZ) that is meaningful in magnitude – 0.13 standard deviations – and statistically significant at the one percent level. For children in the 12–23.9 month age group, ownership of a dairy cow is associated with a 0.37 SD increase in HAZ and a reduction of 11.3 percentage points in stunting. There is no statistically significant association with weight-for-height or wasting. These associations do not differ between boys and girls.